Superconducting Interfaces: Octahedral Distortions at High‐Temperature Superconducting La2CuO4 Interfaces: Visualizing Jahn–Teller Effects (Adv. Mater. Interfaces 24/2017). Issue 24 (21st December 2017) - Suyolcu, Y. Eren; Wang, Yi; Sigle, Wilfried; Baiutti, Federico; Cristiani, Georg; Logvenov, Gennady; Maier, Joachim; van Aken, Peter A.
Abstract : The image is a compilation of the findings presented in the work. It includes the different dopant distribution lengths and Jahn‐Teller distortions observed in Ba‐, Sr‐ and Ca‐doped La2 CuO4 bilayer samples. Distribution lengths for each sample are marked with different colors located on an experimental STEM‐ABF image of the epitaxial layer. Moreover, contracted and expanded CuO6 octahedrals depending on Jahn‐Teller and anti‐Jahn‐Teller distortions are illustrated with consistent color coding. More details can be found in article number1700737 by Y. Eren Suyolcu and co‐workers.